In the heart of the sea [videorecording (Blu-Ray)] - Leavitt, Charles; Hemsworth, Chris; Walker, Benjamin, 1982-; Murphy, Cillian, 1976-; Philbrick, Nathaniel (Warner Home Video, 2016)
In the winter of 1820, the New England whaling ship Essex was assaulted by something no one could believe: a whale of mammoth size and will, and an almost human sense of vengeance. The real-life maritime disaster would inspire Herman Melville's Moby-Dick. But that told only half the story. This story reveals the encounter's harrowing aftermath, as the ship's surviving crew is pushed to their limits and forced to do the unthinkable to stay alive.